Relationship between the composition and hydration-microstructure-mechanical properties of cement-metakaolin-limestone ternary system. (4th October 2021) - Drissi, Sarra; Shi, Caijun; Li, Ning; Liu, Yiwei; Liu, Jianhui; He, Pingping
Highlights: Simplex design method was used to elucidate the composition-dependent mechanism. Composition changes and properties were correlated via graphical visualization. Relationships between the paste composition and its properties were developed. Abstract: This paper aims to elucidate the effect of changes in the mix composition on the properties of Portland cement (PC)-metakaolin (MK)-limestone (LS) ternary system. To achieve this, the mixture proportion was optimized using the simplex design method and its effect on the properties of the binder was evaluated experimentally and correlated via graphical visualization. Experimental results confirmed the enhancement and acceleration of kinetics of cement hydration by LS and MK. However, a higher porosity was noticed at early age and was attributed to the high reactivity of MK which hindered it from acting as an effective filler. Therefore, the correlation between the optimum mix design and compressive strength was found to be dependent on the paste age. The findings of this paper would contribute to a better understanding of the dependence of the properties of PC-MK-LS ternary system on its composition.